The Smoking Behaviors of Indigenous Taiwanese: Individual and Family/Community Factors of Influence - 陳杏雯(Hsing-Wen Chen); 祝年豐(Nain-Feng Chu); 陳興夏(Hsing-Hsia Chen); 葉美玲(Mei-Ling Yeh) (The Journal of Nursing Research, 2014)
BACKGROUND:Smoking, a self-selected behavior, is the sixth leading cause of death worldwide. Factors related to smoking in Taiwan’s indigenous Malayo-Polynesian population should be elicited and addressed. PURPOSE:This study examined the relationship between smoking behavior and individual and family/community factors in indigenous Taiwanese. METHODS:This study was a secondary analysis of data obtained from household visits in central Taiwan that included a population of 562 indigenous adults aged 20–50 years. Data were analyzed using the chi-square test and hierarchical logistic regression to determine individual and family/community relevant factors of smoking behaviors. RESULTS:The smoking rate in the population studied was 57.48% (39.15% men, 18.33% women). The odds ratio for smoking was markedly higher in men than in women. Smokers were 0.45 times more likely to have fixed sexual partners. The OR for smoking was 2.68 times in households with smokers and 7.03 times in people living in mountainous areas. CONCLUSIONS:The issue of smoking in indigenous Taiwanese deserves further attention and concern. Further interventions for the harmful effects of tobacco can focus on younger indigenous people living in mountain regions and on smokers’ sexual partners. In addition, male adults, female adults, and heads of households should take a greater role in changing the smoking behaviors of smokers and their family members.